Ceasing the use of the highest priority critically important antimicrobials does not adversely affect production, health or welfare parameters in dairy cows. (14th July 2018) - Turner, Andrea; Tisdall, David; Barrett, David C; Wood, Sarah; Dowsey, Andrew; Reyher, Kristen K
Abstract : Due to scientific, public and political concern regarding antimicrobial resistance (AMR), several EU countries have already taken steps to reduce antimicrobial (AM) usage in production animal medicine, particularly that of the highest priority critically important AMs (HP‐CIAs). While veterinarians are aware of issues surrounding AMR, potential barriers to change such as concerns of reduced animal health, welfare or production may inhibit progress towards more responsible AM prescribing. Farmers from seven dairy farms in South West England engaged in changing AM use through an active process of education and herd health planning meetings. Prescribing data were collected from veterinary sales records; production and health data were accessed via milk recording and farm‐recorded data. This study demonstrates that cattle health and welfare—as measured by production parameters, fertility, udder health and mobility data and culling rates—can be maintained and even improved alongside a complete cessation in the use of HP‐CIAs as well as an overall reduction of AM use on dairy farms. This study also identified a need to consider different metrics when analysing AM use data, including dose‐based metrics as well as those of total quantities to allow better representation of the direction and magnitude of changes in AM use.